Efficacy and safety of avatrombopag in the treatment of chemotherapy-induced thrombocytopenia in children with acute lymphoblastic leukemia: a single-center retrospective study - Huiyan Yang; Jingyu Gao; Yongsheng Ruan; Zhaokun Chen; Ruihan Fang; Lei Zhang; Zhibiao Wang; Tiantian Yi; Qian Zhang; Yang Luo; Libai Chen; Xuedong Wu (Therapeutic Advances in Hematology)
Background: Chemotherapy-induced thrombocytopenia (CIT) commonly exacerbates the difficulty of cancer treatment, increasing bleeding risks and potentially reducing chemotherapy dosage, ultimately impacting its efficacy. However, there are limited studies about avatrombopag application in acute lymphoblastic leukemia (ALL) CIT. Objectives: We aimed to evaluate the efficacy and safety of avatrombopag in treating CIT patients diagnosed with ALL. Design: This retrospective study, using propensity score matching, included 42 pairs of cases treated with and without avatrombopag (CAT: 54 cases, CAT+: 30 cases). Methods: Data of CIT-ALL children were retrospectively collected. The primary endpoint was platelet count (PC) response rate on day 10 ± 2 (defined as an increase of PC to ⩾75 × 10 9 /L with the exclusion of platelet transfusion). Secondary efficacy endpoints, safety endpoints, and factors that predict PC response were also analyzed. Results: In the avatrombopag group, the PC response rate was prominently higher on day 10 ± 2 (89.1%) versus the control group (56.4%, p = 0.005). On day 10 ± 2, the difference in median PC change from baseline was predominantly distinct in the avatrombopag group compared to the control group ( p = 0.001). In the avatrombopag group, platelet recovery to ⩾25 and ⩾50 × 10 9 /L was faster ( p = 0.001, p = 0.002), and quicker platelet reaching ⩾75 × 10 9 /L and ⩾100 × 10 9 /L was achieved ( p = 0.023, p = 0.011). The avatrombopag group not only increased the nadir PC ( p = 0.009) but also reduced the total platelet transfusion compared to the control group ( p = 0.047). Only one case (2.4%) experienced bleeding events after medication. Nine cases of secondary thrombocythemia were noted without other adverse events. There was no difference in event-free survival between the two groups ( p = 0.648). Drug administration was prediction factor for PC response. Conclusion: Avatrombopag is a potentially safe and effective treatment option for CIT in pediatric ALL.